Bronchial or Laryngeal Obstruction Induced by Exercise? - Bey, Ayoub; Botti, Sophie; Coutier-Marie, Laurianne; Bonabel, Claude; Metche, Stéphanie; Demoulin-Alexikova, Silvia; Schweitzer, Cyril Etienne; Marchal, François; Coffinet, Laurent; Ioan, Iulia (Frontiers in Pediatrics, 2017)
A child suspected of exercise induced laryngeal obstruction and asthma is examined by laryngoscopy and respiratory resistance (Rrs) after exercise challenge. Immediately at exercise cessation, the visualized adduction of the larynx in inspiration is reflected in a paroxystic increase in Rrs. While normal breathing has apparently resumed later on during recovery from exercise, the pattern of Rrs in inspiration is observed to reoccur following a deep breath or swallowing. The procedure may thus help diagnosing the site of exercise induced obstruction when laryngoscopy is not available and identify re-inducers of laryngeal dysfunction.